BBGKY Hierarchy and Dynamics of Correlations - Polishchuk, D.O. (Український фізичний журнал, 2010)
We derive the BBGKY hierarchy for the Fermi and Bose manyparticle systems, using the von Neumann hierarchy for the correlation operators. The solution of the Cauchy problem of the formulated hierarchy in the case of an n-body interaction potential is constructed in the space of sequences of trace-class operators. Виведено iєрархiю ББГКI для Фермi та Бозе багаточастинкових систем на основi iєрархiї фон Неймана для кореляцiйних операторiв. Побудовано розв’язок задачi Кошi сформульованої iєрархiї у випадку n-частинкового потенцiалу взаємодiї для початкових даних iз простору послiдовностей ядерних операторiв.